African American Females Addressing Challenges and Nurturing the Future - Zamani-Gallaher, Eboni M.; Polite, Vernon C. (Michigan State University Press, 2013)
African American Females: Addressing Challenges and Nurturing the Future illustrates that across education, health, and other areas of social life, opportunities are stratified along gender as well as race lines. The unequal distribution of wealth, power, and privilege between men and women intersects with race and class to create multiple levels of disadvantage. This book is one result of a unique forum intended to bring into focus the K-12 and postsecondary schooling issues and challenges affecting African American girls and women. Focusing on the historical antecedents of African American female participation and the contemporary context of access and opportunity for black girls and women, the contributors to this collection pay particular attention to the interaction of gender with race/ethnicity, class, age, and health, with the central aim of encouraging thoughtful reading, critical thinking, and informed conversations about the necessity of exploring the lives of African American females. Additionally, the book frames important implications for recommended changes in policy and practice regarding a number of critical matters presently affecting African American females in schools and communities across the state of Michigan and nationwide.